New Experiences, New Landscapes, New Texts: A Cultural Awakening? - A Study On The Poems In Time Will Write A Song For You - Shriganeshan, K. (Faculty of Management Studies and commerce, University of Jaffna, Sri Lanka, 2015)
Sri Lanka Tamil poetry has already seen the shift from the traditional themes to the very modern ones and from the lyrical from to the free verse. The themes like displacement, exile, death, disfigurement, resistance, and alienation have found their ways into the modern poems. The lyrical quality observed in Mahakavi, Murugian, Neelavanan, Sanmugam Sivalingam and SOPA has not been followed by many a new poet. While the new poets of the 80s and the 90s accommodated the new themes that emerged after the way, the diaspora has found a new landscape of the colder regions and added a sixth to the list of five thinai categories. Thus, there seems to be a space for the marginalized exploited by the new Tamil poets of the late 20th Century. The present study attempts to see whether the poems included in the anthology titled Time will Write a Song for you: Contemporary Tamil Writing from Sri Lanka published by Penguin Books India in association with French Institute of Pondicheri(2014) would open a new space for a cultural awakening.